Admission Decision-Making in Hospital Emergency Departments: The Role of the Accompanying Person. (June 2020) - Rance, Susanna; Westlake, Debra; Brant, Heather; Holme, Ingrid; Endacott, Ruth; Pinkney, Jonathan; Byng, Richard
In resource-stretched emergency departments, people accompanying patients play key roles in patients' care. This article presents analysis of the ways health professionals and accompanying persons talked about admission decisions and caring roles. The authors used an ethnographic case study design involving participant observation and semi-structured interviews with 13 patients, 17 accompanying persons and 26 health care professionals in four National Health Service hospitals in south-west England. Focused analysis of interactional data revealed that professionals' standardization of the patient–carer relationship contrasted with accompanying persons' varied connections with patients. Accompanying persons could directly or obliquely express willingness, ambivalence and resistance to supporting patients' care. The drive to avoid admissions can lead health professionals to deploy conversational skills to enlist accompanying persons for discharge care without exploring the meanings of their particular relationship with the patients. Taking a relationship-centered approach could improve the attention to accompanying persons as co-producers of health care and participants in decision-making.